2005
DOI: 10.2514/1.7549
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Order Modeling of Unsteady Flows Without Static Correction Requirement

Abstract: A new reduced-order modeling approach is presented. This approach is based on fluid eigenmodes and without using the static correction. The vortex lattice method is used to analyze unsteady flows over two-dimensional airfoils and three-dimensional wings. Eigenanalysis and reduced-order modeling are performed using a conventional method with and without the static correction technique. In addition to the conventional method, eigenanalysis and reduced-order modeling are also performed using the new proposed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Pervious works (Esfahanian and Behbahani-Nejad, 2002;Behbahani-Nejad et al, 2005) have shown that the existence of zero eigenvalues in the eigensystem is the main reason for needing to apply a static correction technique. Hence, by constructing a reduced-order model based only on the wake eigenmodes, the body quasi-static eigenmodes can be removed.…”
Section: Present Reduced-order Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pervious works (Esfahanian and Behbahani-Nejad, 2002;Behbahani-Nejad et al, 2005) have shown that the existence of zero eigenvalues in the eigensystem is the main reason for needing to apply a static correction technique. Hence, by constructing a reduced-order model based only on the wake eigenmodes, the body quasi-static eigenmodes can be removed.…”
Section: Present Reduced-order Modellingmentioning
confidence: 99%
“…By constructing a reduced-order model based only on the wake eigenmodes, the body quasi-static eigenmodes are removed and it is possible to obtain satisfactory results without the static correction technique. This concept has been recently applied by Behbahani-Nejad et al (2005) for unsteady flow computations based on the vortex lattice method.…”
Section: Introductionmentioning
confidence: 98%
“…ROM gave lower computational cost and reduced time for computation. ROM was recently used in the analysis of unsteady flows [21]. Agaie and Amin [22] used the ROM technique to study the effect of water hammer on transportation of hydrogen-natural mixture.…”
Section: Introductionmentioning
confidence: 99%
“…17. As stated in [1], the zero (29), respectively) to a step change in angle of attack is shown in Fig. 18.…”
Section: Rom For Continuous Form Of An Aeroelastic Airfoilmentioning
confidence: 98%
“…Γ is a vector containing vortex strengths. Behbahani-Nejad et al [1] investigation show the aerodynamics equation in the form of (13) has some zero eigenvalues which makes some problem in constructing the reduced order aerodynamics model. They modified this model and named it as the modified vortex lattice model.…”
Section: Discrete Form Of the Aerodynamics Equationsmentioning
confidence: 99%